IDENTIFIKASI MUTASI GEN rpoB PADA ISOLAT Mycobacterium tuberculosis MULTIDRUG RESISTANT DENGAN METODE NESTED POLYMERASE CHAIN REACTION - Wijaya, Made Dharmesti; Rusyanthini, Eka Putri; Pradnyaniti, Desak Gede; Komalasari, Komang Trisna; Sunarti, Luh Putu Suci Sri (Program Kreativitas Mahasiswa - Penelitian, 2013)
The rpoB gene has been known to be a surrogate marker for detection of Multidrug Resistant Tuberculosis (MDR-TB). Mutations of rpoB gene were associated with rifampicin (RMP) resistance occur in 81 bp region called Rifampin Resistance-Determining Region (RRDR). This study was aimed to determine the types of mutations and amino acid differences in isolates of M.tuberculosis MDR compared to M.tuberculosis H37Rv. Amplification of rpoB gene fragments was carried out using nested Polymerase Chain Reaction (nested PCR). Analysis of mutation using MEGA4 showed two amino acid changes namely, E418D and H526L. The type of mutations determined in isolate was missense mutations. Keywords: MDR-TB, mutation, nested PCR, rpoB